2020
DOI: 10.1101/2020.06.15.20129411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early impacts of the COVID-19 pandemic on mental health care and on people with mental health conditions: framework synthesis of international experiences and responses

Abstract: Purpose The COVID-19 pandemic has many potential impacts on people with mental health conditions and on mental health care, including direct consequences of infection, effects of infection control measures and subsequent societal changes. We aimed to map early impacts of the pandemic on people with pre-existing mental health conditions and services they use, and to identify individual and service-level strategies adopted to manage these. Methods We searched for relevant material in the public domain publishe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 27 publications
9
109
1
Order By: Relevance
“…Our questionnaire was by necessity an ad hoc and not an established and validated tool. Omissions were noted as the study progressed: it was assumed that impacts of the “lockdown” for service users were negative, but positive experiences are noted too, for example of reduced pressure or easier access for people who struggle to travel [ 13 ]. More importantly, we designed the questionnaire early in the pandemic when the evidence of differential effects on some ethnic groups was less striking [ 19 ]: closed questions do not focus on this, although these effects and issues of racism are included in open-ended responses on concerns for the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our questionnaire was by necessity an ad hoc and not an established and validated tool. Omissions were noted as the study progressed: it was assumed that impacts of the “lockdown” for service users were negative, but positive experiences are noted too, for example of reduced pressure or easier access for people who struggle to travel [ 13 ]. More importantly, we designed the questionnaire early in the pandemic when the evidence of differential effects on some ethnic groups was less striking [ 19 ]: closed questions do not focus on this, although these effects and issues of racism are included in open-ended responses on concerns for the future.…”
Section: Discussionmentioning
confidence: 99%
“…The lead developer of the questionnaire, SJ, an academic and practising inner London psychiatrist, read key sources identified in an accompanying rapid review of relevant literature [ 13 ], including academic and professional journals, news media, and organisational websites, and followed relevant social media topics. The drafting of the questionnaire was further informed by the NIHR Mental Health Policy Research Unit (PRU) working group for this study (about 30 people, including clinicians, researchers, and people with relevant lived experience), and the PRU Lived Experience Working Group.…”
Section: Methodsmentioning
confidence: 99%
“…The pervasive contagion, along with the consequent widespread fear and the necessary containment measures to limit the outbreak (e.g. quarantine and lockdown), is likely to lead psychological consequences in the general population, but the distress in people with pre-existing psychiatric conditions is likely to have been greater [ 1 , [3] , [4] , [5] ]. Although general literature provides evidence of a greater susceptibility of psychiatric patients to environmental stress related to trauma [ 1 , 6 , 7 ], a recent review focusing on the psychological impact of quarantine included only one study considering mental illness as a risk factor [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Although general literature provides evidence of a greater susceptibility of psychiatric patients to environmental stress related to trauma [ 1 , 6 , 7 ], a recent review focusing on the psychological impact of quarantine included only one study considering mental illness as a risk factor [4] . Studies suggest that psychiatric patients seem to be at high risk of infection, due to pre-existing disorders, unhealthy lifestyle, cognitive impairment or reduced level of awareness of the risk [ 3 , 8 , 9 ]. In contrast, recent findings from United Kingdom (UK) indicated that mentally-ill patients were at lower risk of contracting the infection compared to general population [10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation